Effects of moxibustion on cognition and activities of daily living in post‐stroke cognitive impairment: A systematic review and meta‐analysis of randomized controlled trials. Issue 2 (8th November 2022) - Liu, Fang; Lyu, Zecai; Lin, Shaohong; Li, Zhuangmiao; Xiu, Huoqin
Abstract: Background: Post‐stroke cognitive impairment (PSCI) imposes a huge burden on patients and society as a whole; however, unequivocally effective treatments for PSCI are still lacking. Therefore, the exploration of effective and safe non‐pharmacological treatment modalities for PSCI is a key imperative. Moxibustion has been widely used for cognitive rehabilitation; however, there is a paucity of systematic reviews of the available evidence. Therefore, we conducted a systematic review and meta‐analysis of randomized controlled trials (RCTs) that investigated the effectiveness of moxibustion for treatment of PSCI to provide evidence base for the treatment of PSCI with moxibustion. Objective: To evaluate the efficacy of moxibustion in improving cognitive function and activities of daily living (ADLs) in patients with PSCI. Design: Systematic review and meta‐analysis of RCTs. Participants: Patients with a clinical diagnosis of PSCI. Review Methods: Relevant studies published in English or Chinese were retrieved from ten databases until December 2021. RCTs that assessed the efficacy of moxibustion on cognitive functioning and ADL in patients with PSCI were included. Two reviewers independently identified the trials and extracted the data. Risk‐of‐bias was assessed using the Cochrane Risk of Bias Tool. Cochrane's Review Manager (RevMan 5.4) software was used for the meta‐analysis. Results: Eighteen RCTs (1290 participants) qualified the inclusion criteria and were included. Compared with the control group, the addition of moxibustion significantly improved the cognitive function, evaluated using the Montreal Cognitive Assessment (MoCA) [pooled mean difference (MD): 2.27, 95% CI: 1.98, 2.55, I 2 = 22%]. The pooled MD of Mini‐Mental State Examination (MMSE) score was 1.85 (95% CI: 1.56, 2.15, I 2 = 26%), and the pooled odds ratios (OR) total effective rate was 4.74 (95% CI: 2.55, 8.80, I 2 = 0%) ( p < 0.05 for all). Moxibustion also significantly improved ADL, assessed using Modified Barthel Index (MBI) (pooled MD = 4.10, 95% CI: 2.10 to 6.10, I 2 = 0%) and Barthel Index (pooled MD: 8.63, 95% CI: 7.47, 9.79, I 2 = 5%) ( p < 0.05 for all). Conclusions: Compared with control group, the addition of moxibustion significantly improved the cognition and ADL of patients with PSCI. Clinical Relevance: Nurses can incorporate moxibustion into the rehabilitation nursing of PSCI.